2020
DOI: 10.1590/0100-3984.2019.0089
|View full text |Cite
|
Sign up to set email alerts
|

Subspecialized radiology reporting: productivity and impact on the turnaround times for radiology reports in a middle-income country

Abstract: Objective: To evaluate the effect that transitioning from a model of general radiology reporting to one of subspecialized radiology reporting has on report turnaround times (TATs) and on productivity in the radiology department of a hospital in a middle-income country. Materials and Methods: The reporting workflow in our radiology department was changed from general reporting (any radiologist reporting imaging studies for any specialty) to subspecialized reporting (radiologists exclusively reporting imaging s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A comprehensive and thorough musculoskeletal radiology education is essential for both general and sub-specialised radiologists, given that the former may deal with musculoskeletal examination in emergency departments or outpatient scans, while the latter must support clinical activity of highly specialised orthopaedists, rheumatologists, and other physicians in referral centres [ 22 ]. Notably, authors have highlighted that subspecialists are more accurate in about 80% of reports than general radiologists, particularly concerning oncologic examinations [ 3 ]; this is something that was also highlighted by Rozenberg and associates in reporting scans about musculoskeletal tumours [ 23 ]. Further, authors have shown that young trainees who underwent a dedicated musculoskeletal training period substantially improved their performance in bone densitometry interpretation, thereby impacting the start of osteoporosis treatment with drugs [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive and thorough musculoskeletal radiology education is essential for both general and sub-specialised radiologists, given that the former may deal with musculoskeletal examination in emergency departments or outpatient scans, while the latter must support clinical activity of highly specialised orthopaedists, rheumatologists, and other physicians in referral centres [ 22 ]. Notably, authors have highlighted that subspecialists are more accurate in about 80% of reports than general radiologists, particularly concerning oncologic examinations [ 3 ]; this is something that was also highlighted by Rozenberg and associates in reporting scans about musculoskeletal tumours [ 23 ]. Further, authors have shown that young trainees who underwent a dedicated musculoskeletal training period substantially improved their performance in bone densitometry interpretation, thereby impacting the start of osteoporosis treatment with drugs [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the era of precision medicine, we are witnessing a constant shift toward more subspecialised physicians and clinical activities, which is something occurring in all fields of radiology, particularly in musculoskeletal (MSK) imaging [ 1 , 2 , 3 ]. This is probably due to the ongoing introduction of novel technologies, the improvements in knowledge, and the increasing expectations of other specialists for more and more accurate diagnosis through imaging [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The growing level of detail and complexity of imaging studies contributes to this divergence. Additionally, some authors have reported reduced turn-around times (TATs) for sub-specialized radiologists when working in their respective fields [ 16 , 17 ]. Evaluating the need for sub-specialization in radiology is, therefore, a discussion about quality as well as quantity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%